Ethnomedicinal uses, pharmacological activities, and cultivation of Lignosus spp. (tiger׳s milk mushrooms) in Malaysia – A review. (1st July 2015) - Lau, Beng Fye; Abdullah, Noorlidah; Aminudin, Norhaniza; Lee, Hong Boon; Tan, Pei Jean
Abstract: Ethnopharmacological relevance: Several members of the genus Lignosus, which are collectively known as cendawan susu rimau (in Malay) or tiger׳s milk mushrooms (TMM), are regarded as important local medicine particularly by the indigenous communities in Malaysia. The mushroom sclerotia are purportedly effective in treating cancer, coughs, asthma, fever, and other ailments. The most commonly encountered Lignosus spp. in Malaysia was authenticated as Lignosus rhinocerotis (Cooke) Ryvarden (synonym: Polyporus rhinocerus ), which is also known as hurulingzhi in China and has been used by Chinese physicians to treat liver cancer, gastric ulcers, and chronic hepatitis. In spite of growing interest in the therapeutic potential of TMM, there is no compilation of scientific evidence that supports the ethnomedicinal uses of these mushrooms. Therefore, the present review is intended (i) to provide a comprehensive, up-to-date overview of the ethnomedicinal uses, pharmacological activities, and cultivation of TMM in general and L. rhinocerotis in particular, (ii) to demonstrate how recent scientific findings have validated some of their traditional uses, and (iii) to identify opportunities for future research and areas to prioritize for TMM bioprospecting. Materials and methods: A detailed literature search was conducted via library search (books, theses, reports, newspapers, magazines, and conference proceedings) and electronic search (Web of Science, PubMed, and Google Scholar) for articles published in peer-reviewed journals. These sources were scrutinized for information on TMM and specifically for L. rhinocerotis . Results: Ethnomycological knowledge about TMM, with an emphasis on cultural associations and use as local medicine, has been comprehensively and systematically compiled for the first time. Some of the reported medicinal properties of TMM have been validated by scientific studies. The anti-tumor, immuno-modulatory, anti-inflammatory, anti-oxidative, anti-microbial, neurite outgrowth stimulation, and other pharmacological activities of L. rhinocerotis sclerotial extracts have been explored. The nature of sclerotial bioactive components, such as proteins, polysaccharides, and/or polysaccharide–protein complexes, has been identified, whereas the low-molecular-weight constituents remain poorly studied. The artificial cultivation of L. rhinocerotis via solid substrate and liquid fermentations successfully yielded fruiting bodies, sclerotium, mycelium, and culture broth that could be exploited as substitutes for the wild resources. The cultivated sclerotium and mycelium were shown to be safe from a toxicological point of view. Other research areas, e.g., chemical studies, genomics, and proteomics, have been employed to gain insights into the medicinal properties of TMM. Conclusions: This review clarified the medicinal properties of TMM as recorded in various ethnomycological records, and it simultaneously highlighted the current efforts to provide scientific evidence by using various in vitro and in vivo models. Thus far, only the anti-tumor and immuno-modulatory effects of L. rhinocerotis sclerotial aqueous extracts have been extensively investigated, and other medicinal properties relevant to their traditional uses, e.g., anti-tussive and anti-pyretic properties, have yet to be validated. Further studies focusing on (i) the isolation and characterization of active components, (ii) the elucidation of their modes of action, and (iii) an evaluation of their safety and efficacy, when compared with the crude aqueous preparations, are warranted to accelerate potential drug discovery from TMM. Graphical abstract: